2003
DOI: 10.1074/jbc.m203108200
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Function Relationships in the Stereospecific and Manganese-dependent 3,4-Dihydroxyphenylalanine/ Tyrosine-sulfating Activity of Human Monoamine-form Phenol Sulfotransferase, SULT1A3

Abstract: The human monoamine-form phenol sulfotransferase (PST), SULT1A3, has a unique 3,4-dihydroxyphenylalanine (Dopa)/tyrosine-sulfating activity that is stereospecific for their D-form enantiomers and can be stimulated dramatically by Mn 2؉ . This activity is not present in the simple phenol-form PST, SULT1A1, which is otherwise >93% identical to SULT1A3 in amino acid sequence. The majority of the differences between these two proteins reside in two variable regions of their sequences. Through the characterization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 27 publications
(60 reference statements)
0
8
0
Order By: Relevance
“…This interaction would prevent binding of the second dopamine molecule by removing a major protein interaction. This is further supported by the fact that Glu-89 is replaced by isoleucine in SULT1A1, this protein shows very low substrate binding affinity for dopamine, and its activity is unaffected by adding Mn 2ϩ (44,45). The mutation of Glu-89 in SULT1A3 to isoleucine results in reduced activity toward dopamine (42,45).…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…This interaction would prevent binding of the second dopamine molecule by removing a major protein interaction. This is further supported by the fact that Glu-89 is replaced by isoleucine in SULT1A1, this protein shows very low substrate binding affinity for dopamine, and its activity is unaffected by adding Mn 2ϩ (44,45). The mutation of Glu-89 in SULT1A3 to isoleucine results in reduced activity toward dopamine (42,45).…”
Section: Discussionmentioning
confidence: 58%
“…This is further supported by the fact that Glu-89 is replaced by isoleucine in SULT1A1, this protein shows very low substrate binding affinity for dopamine, and its activity is unaffected by adding Mn 2ϩ (44,45). The mutation of Glu-89 in SULT1A3 to isoleucine results in reduced activity toward dopamine (42,45). In the SULT1A3 crystal structure (15), residues 86 -90 form a mobile loop that intercalates into the active site of a symmetry-related monomer.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…SULT1A3 has a unique dopa (3,4-dihydroxyphenylalanine; 17 , Fig.1)-sulfating activity that was stereo-selective for their D-form enantiomers [38]. Although there is a lack of experimentally derived differentiation between the formation rates of different sulfated metabolites, molecular docking of D-dopa to the SULT1A3 crystal structure rendered the 3-OH group of D-dopa at a closer position to the catalytic residues than 4-OH, suggesting that 3-O-sulfate should be preferentially generated by SULT1A3 [17].…”
Section: Regioselective Sulfation Of Phenolicsmentioning
confidence: 99%
“…In this case, the enhanced specificity of SULT1A3 for catecholamines relative to 4-nitrophenol and the reverse specificity with SULT1A1 were linked to a glutamate residue (Glu146) in SULT1A3 that corresponds to an alanine in SULT1A1 (Dajani et al, 1998(Dajani et al, , 1999Brix et al, 1999). Additional investigations on SULT1A1 and SULT1A3 have indicated that Glu146 as well as residues 84 -90 are implicated in the stereospecific sulfation of the D-isomers of DOPA and tyrosine (Pai et al, 2003).…”
Section: Stereospecificity Of Aryl Sulfotransferase IVmentioning
confidence: 99%